Analisis Kendala Profesionalisme Guru tersertifikasi Pendidik dalam Pembelajaran Daring Masa Pandemi Covid-19 di Kabupaten Sikka - Sonya Kristiani; Paulina Nelce Mole (Peneliti.net, 2021)
This study aims to find out the obstacles to the professionalism of certified educators faced by teachers when carrying out online learning during the Covid-19 pandemic. The methods used are interviews and qualitative descriptive. The subjects of this research are professional teachers who have been certified educators in several senior high schools in Sikka Regency. The results showed that the obstacles experienced by teachers during teaching in online learning were that many students could not participate in learning activities. This was due to the lack of facilities owned by students when learning online because not all students had smartphones as learning media using online. can follow because the internet network is not good.